Depression and Creativity During COVID-19: Psychological Resilience as a Mediator and Deliberate Rumination as a Moderator - Xu, Yanhua; Shao, Jinlian; Zeng, Wei; Wu, Xingrou; Huang, Dongtao; Zeng, Yuqing; Wu, Jiamin (Frontiers in Psychology, 2021)
Purpose: The pandemic of novel coronavirus pneumonia (COVID-19), which has had a significant impact on people's lives, has apparently increased the incidence of depression. Although the topic of how depression affects creativity is contested, previous research has revealed a significant relationship between the two. The purpose of this study is to further investigate the relationship and the mechanisms that operate between depression and creativity. Methods: A total of 881 students at an independent college in China completed a questionnaire consisting of the Self-Reported Depression Scale, Runco Ideational Behavior Scale, Psychological Resilience Scale, Deliberate Rumination Scale and demographic information. Correlation analyses were conducted, and then the researchers carried out mediation analysis and developed a moderated mediation model. Results: The results indicated that (a) depression was positively related to creativity; (b) psychological resilience mediated the relationship between depression and creativity; specifically, depression was negatively related to psychological resilience, which in turn was positively related to creativity; and (c) deliberate rumination moderated the relationship between depression and psychological resilience; specifically, higher levels of deliberate rumination strengthened the negative correlation between psychological resilience and deliberate rumination. Conclusions: The results suggest that depression is, to some extent, a stimulus for creativity. Further, individuals with greater psychological resilience are more creative than those with less psychological resilience, as it is a question of whether they can and to what extent they can effectively use depression as an emotional resource. Last, an individual's level of deliberate rumination moderates the mediating process, especially at the stage where depression is associated with psychological resilience. These findings advance understanding of the mechanisms that operate between depression and creativity.